Penerapan Game Interaktif Aplikasi Kahoot untuk Meningkatkan Minat Belajar Matematika Siswa - Efendi, Annisa Mulya; Yudhi, Prima; Ergusni, Ergusni (Lattice Journal : Journal of Mathematics Education and Applied, 2022)
Effective learning is student-centered learning. This is because students are the center of learning. Student involvement in learning is of course very meaningful to provide experience for students. Some efforts to involve students in learning are using learning media. Appropriate learning media must be adapted to the needs of students in the class. The learning carried out at SMK N 1 Batipuh is based on the results of needs and material analysis that students show more enthusiasm for learning when using media. One of the right media is the interactive game application kahoot which means that the media can be accessed easily by students. The kahoot application interactive game can increase student interest in learning because it is multimedia in nature and is a "challenge" between students. The purpose of this study was to find out that the application of interactive games, the kahoot application, can increase the interest in learning mathematics for class XI students of SMKN 1 Batipuh. This type of research is experimental research using experimental methods, which is used is the T test. Data collection techniques using questionnaires.Â Pembelajaran efektif ialah pembelajaran yang terpusat pada siswa. Hal ini dikarenakan siswa adalah pusat pembelajaran. Keterlibatan siswa dalam pembelajaran tentu sangat berarti untuk memberi pengalaman bagi siswa. Beberapa upaya untuk melibatkan siswa dalam pembelajaran ialah menggunakan media pembelajaran. Media pembelajaran yang tepat tentu harus disesuaikan dengan kebutuhan siswa di kelas tersebut. Pembelajaran yang dilaksanakan di SMK N 1 Batipuh berdasarkan hasil analisis kebutuhan dan materi bahwa siswa lebih menunjukkan antusias belajar jika menggunakan media. Salah satu media yang tepat ialah game interaktif aplikasi kahoot yang berarti media tersebut bisa di akses dengan mudah oleh siswa. Game interaktif aplikasi kahoot dapat meningkatkan minat belajar siswa karena bersifat multimedia dan bersifat â€œchallengeâ€ antarsiswa. Tujuan penelitian ini ialah mengetahui penerapan game interaktif aplikasi kahoot dapat Â meningkatkan minat belajar matematika siswa kelas XI SMKN 1 Batipuh. Jenis penelitian ini adalah penelitian eksperimen dengan menggunakan metode eksperimen, yang digunakan ialah Uji T. Teknik pengumpulan data dengan menggunakan angket.